2020
DOI: 10.1111/dth.14512
|View full text |Cite
|
Sign up to set email alerts
|

Is chemoprophylaxis necessary for all latent tuberculosis infection patients receivingIL‐17 inhibitors? A cohort study

Abstract: The tuberculosis (TB) burden is high in China, with a 32% prevalence of latent tuberculosis infection (LTBI) in Beijing. Screening for LTBI and the chemoprophylaxis of positive patients are recommended prior to biologic therapy. To evaluate the TBrelated safety of secukinumab (SEC) in a cohort of plaque psoriasis patients with LTBI receiving different treatments. Plaque psoriasis patients eligible for SEC treatment were screened for TB. LTBI patients (QuantiFeron-TB test positive, QFT+) receiving SEC were clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…An Italian real-life study on 12 patients with LTBI showed no reactivation on secukinumab without previous prophylactic treatment after a 52-week follow-up ( 6 ). Further real-life studies have reported regular follow-up in LTBI patients treated with secukinumab without prophylactic therapy, despite 10 cases of QTF positivity during treatment ( 21 , 41 , 42 ). In the current series, 11 patients have taken secukinumab, and 6 are still currently on it.…”
Section: Discussionmentioning
confidence: 99%
“…An Italian real-life study on 12 patients with LTBI showed no reactivation on secukinumab without previous prophylactic treatment after a 52-week follow-up ( 6 ). Further real-life studies have reported regular follow-up in LTBI patients treated with secukinumab without prophylactic therapy, despite 10 cases of QTF positivity during treatment ( 21 , 41 , 42 ). In the current series, 11 patients have taken secukinumab, and 6 are still currently on it.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed no change in the lung pathology (calcification). As reported in the literature, patients with latent TB who received no chemoprophylaxis could be safely treated with secukinumab ( 1 , 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…to its high PASI response rate, 11 better safety in terms of inducing infection compared with TNF-α inhibitors, 12 and coverage by medical insurance, etc.…”
Section: Discussionmentioning
confidence: 99%